Ragam Bentuk Pelanggaran Ajaran Islam Dalam Kehidupan Pelajar - Syakirah, Rahma Dhita; Fakhruddin, Agus (Yayasan Rahmat Islamiyah, 2024)
Islamic education plays a crucial role in shaping the character and morality of students. However, the increasing prevalence of violations against Islamic teachings, such as brawls, drug abuse, and other immoral behaviors, has become a major concern in the field of education. This study is a literature review that examines the various forms of violations of Islamic teachings among students, as well as their impact on their social and spiritual lives. The study found that factors such as cultural globalization, lack of self-control, and weak inculcation of religious values are the main causes of the decline in students' morality. To address these issues, an education system that focuses on noble character and the consistent implementation of Islamic law is essential. The findings of this study are expected to serve as a reference in the development of more effective educational policies in shaping a generation with strong moral integrity.